Nursing care for mother-child in postpartum depression (Research, Society and Development, 2024)
Postpartum depression poses a problem for the health of the mother-child dyad, capable of causing various emotional and behavioral changes in women, as well as in the development and interaction of mother and child. Nursing care in the postpartum period focuses on screening for depression through follow-ups, individual and group sessions, and educational activities. Objective: To analyze the impact of postpartum depression on the mother-child dyad and the role of nursing in caring for women with postpartum depression. Methodology: This is an integrative review that used the PICO strategy to search for scientific articles. Publications were searched in the databases BVS, LILACS, BDENF, and SciELO, including articles from 2011 to 2021. Fifteen studies were selected from 1765 publications. Results: Most articles highlighted the importance of identifying signs and symptoms of depression, particularly guilt, anxiety, and distress. Some studies pointed out that among the main challenges were: lack of continuous professional training, absence in practice of support with a defined flowchart for the diagnosis of postpartum depression. Conclusion: Nursing follow-up is essential to identify signs and symptoms of depression or anxiety within the Family Health Strategy, as well as risk factors that may affect maternal mental health. Screening strategies, such as the use of postpartum depression assessment scales, have been shown to be effective in identifying various symptoms of clinical depression.